The relative risk of clinically relevant cholelithiasis among glucagon-like peptide-1 receptor agonists in patients with type 2 diabetes mellitus, real-world study - Mohammed Ali Gameil; Elshahat Ali Ahmed Mohamed Yousef; Rehab Elsayed Marzouk; Mohamed H. Emara; Abeer H. Abdelkader; Rasha Ibrahim Salama (Diabetology & Metabolic Syndrome)
Abstract Background and Aim The association between biliary disorders with weight reduction enhanced by GLP-1RAs was observed frequently, nevertheless, the relative risk of the clinically relevant cholelithiasis was not specified clearly among different GLP-1RAs. Methods 308 patients with type 2 diabetes mellitus (T2D) were recruited and divided into 4 groups; liraglutide, dulaglutide, semaglutide, versus control group; comprised of 69, 76, 71, and 92, respectively. Clinical history, examination, laboratory, and radiology tests were implemented. Results Cholelithiasis significantly associates GLP1-RAs (p = 0.033). Overall cholelithiasis was evident in 31.2% of our participants. Symptomatic cholelithiasis prevails in 60.4% of patients with cholelithiasis. Symptomatic complicated cholelithiasis prevailed in 33.3%; distributed in 28.1%, 28.1%, 21.9%, and 21.9% in liraglutide, semaglutide, dulaglutide, and control groups, respectively. Meanwhile, symptomatic uncomplicated cholelithiasis was observed in 27.1%; distributed in 34.6%, 30.8%, 15.4%, and 19.2% in Liraglutide, semaglutide, dulaglutide, and control groups, respectively. Asymptomatic cholelithiasis was noted in 36.8%, 21.1%, 10.5%, and 31.6% of patients with dulaglutide, semaglutide, liraglutide, and control groups, respectively. Specifically, 81.1%, 68%, and 44% of patients with liraglutide, semaglutide, and dulaglutide experienced symptomatic cholelithiasis. The relative risk of cholelithiasis was 1.2, 1.3, and 1.4 in liraglutide, dulaglutide, and semaglutide with number needed to harm of 17.25, 14.69, and 10.96, respectively. The relative risk of symptomatic cholelithiasis was 1.6, 0.9, and 1.4 in liraglutide, dulaglutide, and semaglutide with number needed to harm of 3.14, 16.67, and 5.56, respectively. Conclusion Liraglutide was associated with the highest risk of clinically relevant cholelithiasis than semaglutide, and dulaglutide in patients with T2D.